PENINGKATAN KEMAMPUAN MENGENAL KONSEP ANGKA ANAK USIA 4-5 TAHUN MELALUI GAME INTERAKTIF WORDWALL DI PAUD HIDARA RAMA AGUNG, ARGA MAKMUR, BENGKULU - Rina Melati; Nur Hazizah (LPPM IAD Probolinggo, 2026)
The purpose of this study was to improve early childhood children's ability to recognize number concepts through the use of Wordwall games. The research was conducted at PAUD Hidara Rama Agung. Based on the observation results, there were still children who experienced difficulties in matching number symbols with the quantity of objects, as well as a lack of interest and involvement in learning activities that tended to be monotonous. This study employed the Classroom Action Research method, which was carried out in two cycles. The research subjects consisted of 12 children in Group A (aged 4–5 years). Data collection techniques were conducted through observation and documentation, while data analysis used descriptive qualitative methods. The results of the study showed an improvement in children's ability to recognize number concepts in each cycle. In Cycle I, the average learning mastery reached approximately 55%, with the indicator of mentioning number sequences achieving 50%, recognizing number symbols 41.6%, and matching the number of objects with numbers 33.3%. In Cycle II, there was a significant improvement, where the indicator of mentioning number sequences reached 100%, recognizing number symbols reached 91.67%, and matching the number of objects with numbers reached 83.33%. Therefore, the use of Wordwall interactive games proved to be effective in improving early childhood children's ability to recognize number concepts and can serve as an alternative innovative learning medium to increase children's interest in learning.